Impact of a Nutrition Education Intervention on Salt/Sodium Related Knowledge, Attitude, and Practice of University Students - Cheikh Ismail, Leila; Hashim, Mona; Jarrar, Amjad H.; Mohamad, Maysm N.; Al Daour, Rameez; Al Rajaby, Radhiya; AlWatani, Sara; AlAhmed, Amna; Qarata, Shaikha; Maidan, Fatima; Saleh, Sheima T.; Stojanovska, Lily; et al. (Frontiers in Nutrition, 2022)
1) Background: salt reduction strategies help reduce the risk of cardiovascular diseases (CVDs) by reducing high blood pressure. This study aimed to assess salt related knowledge, attitude, and practices (KAP) before and after administering an evidence-based nutrition education workshop; (2) Methods: 90 non-medical university students were recruited to investigate KAP related to dietary salt intake. The KAP components were assessed before, immediately after, and 4-weeks after administering an evidence-based educational workshop and leaflet; (3) Results: knowledge and attitudes related to salt improved significantly immediately post-intervention but were not fully retained after 4-weeks. Five of the thirteen evaluated practices improved after 4-weeks: trying to buy low-salt foods increased from 10% to 19% (P=0.022), rarely adding salt to food during cooking increased from 5% to 16% (P=0.019), rarely adding salt to food at the table increased from 29% to 42% (P=0.011), tried to reduce salt intake increased from 26% to 41% (P=0.014), and tried to use spices to reduce salt increased from 31% to 45% (P=0.044); (4) Conclusions: the educational intervention had a positive impact on salt-related knowledge, attitudes, and practices, but the effect was not fully retained on the long-term. Periodic educational interventions should be considered to refresh knowledge and reinforce practices.